N-Docosahexaenoylethanolamide promotes development of hippocampal neurons - Hee‐Yong Kim; Hyun‐Seuk Moon; Dehua Cao; Jeongrim Lee; Karl Kevala; Sang Beom Jun; David M. Lovinger; Mohammed Akbar; Bill X. Huang (2011)
DHA (docosahexaenoic acid, C22:6,n-3) has been shown to promote neurite growth and synaptogenesis in embryonic hippocampal neurons, supporting the importance of DHA known for hippocampus-related learning and memory function. In the present study, we demonstrate that DHA metabolism to DEA (N-docosahexaenoylethanolamide) is a significant mechanism for hippocampal neuronal development, contributing to synaptic function. We found that a fatty acid amide hydrolase inhibitor URB597 potentiates DHA-induced neurite growth, synaptogenesis and synaptic protein expression. Active metabolism of DHA to DEA was observed in embryonic day 18 hippocampal neuronal cultures, which was increased further by URB597. Synthetic DEA promoted hippocampal neurite growth and synaptogenesis at substantially lower concentrations in comparison with DHA. DEA-treated neurons increased the expression of synapsins and glutamate receptor subunits and exhibited enhanced glutamatergic synaptic activity, as was the case for DHA. The DEA level in mouse fetal hippocampi was altered according to the maternal dietary supply of n-3 fatty acids, suggesting that DEA formation is a relevant in vivo process responding to the DHA status. In conclusion, DHA metabolism to DEA is a significant biochemical mechanism for neurite growth, synaptogenesis and synaptic protein expression, leading to enhanced glutamatergic synaptic function. The novel DEA-dependent mechanism offers a new molecular insight into hippocampal neurodevelopment and function.